(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Added Value Analysis of Arabica Coffee of Sri Sedana Processing Business Unit, Pelaga Village, Petang District, Badung Regency. Coffee is one of plantation commodities that have high economic value, especially arabica coffee. The way to improve the quality of coffee production is through quality screening (processing from red logs to HS coffee, and HS coffee to OSE coffee). During the harvest season the production of arabica coffee fruit is abundant while the market demand is low, so the price of red coffee tends to decline. As such, many arabica coffee producers choose to process their coffee first. Sri Sedana Processing Business Unit is one of the coffee producers in Bali and the company does so to provide higher added value. The survey method is used to obtain primary data from five respondents of the company’s administrator staff. Secondary data is obtained from trusted sources. Added value in one production cycle is calculated using the Hayami Method. Processing from red logs to HS coffee and from coffee to OSE coffee produces an added value of Rp 3.732,93 and Rp 24.107,93 per kilogram of raw material.